PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU INDOMILK (STUDI PADA KONSUMEN SUSU INDOMILK DI KECAMATAN PURWOSARI, KABUPATEN PASURUAN) - Mochamad Arif Rizky; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT The aim of this research is to find out the effect of price perceptions, product quality, brand image and promotion on purchasing decisions of Indomilk dairy products. The population in this study were consumers who had purchased Indomilk dairy products more than once at Sengon Agung's agent, Purwosari, Pasuruan Regency. This research is a type of descriptive research using a quantitative approach and also uses questionnaire research instruments. The research method used is multiple linear regression. The sample in this study was taken using Slovin formula with purposive sampling technique that is sampling technique with certain considerations where the researcher will take samples with certain criteria, were age between 17-35 years and had bought Indomilk dairy products more than once. A sample of 85 respondents in a population of 550 consumers was obtained. The results showed that price perception (X1) did not significantly influence purchasing decisions with values (Sig 0.649), product quality (X2) significantly affected purchasing decisions with values (Sig 0,000), brand image (X3) had no significant effect on decisions purchase with a value (Sig 0.499), promotion (X4) has no significant effect on purchasing decisions with a value (Sig 0.088). Keyword: Price Perceptions,Product Quality, Brand Image, Promotion and purchasing decisions